Social Media Content and Data Analysis of Audience Engagement in the Tour and Travel Industry - Kurniawan, Yohannes; Harry, -; Oktavianus, Kelvin; Anwar, Norizan; Cabezas, Diego (JOIV : International Journal on Informatics Visualization, 2022)
Social media has become the most popular area where the primary users are the youth generation. Social media marketing has become the best promotion for many companies regardless of the private or public sector, medium or large companies, including Tour and Travel companies. The companies must survive this pandemic by using social media technology to promote their services by creating promotional content that can attract customers' attention on social media, which may help to increase company revenue. This study analyzes the engagement and interaction of promotion content in the context of marketing on social media, such as Instagram, during the Covid-19 pandemic. This research underlines the customer perception about tour and travel content on Instagram for the companies and content characteristics to know the best strategy for doing promotional activities on Instagram through the questionnaire as supporting material. This quantitative research method uses data analytics tools and content analysis methods. This study also obtained data from the official website, journals, books, and articles. This research also utilizes surveys as supporting material focusing on the Instagram data analysis using content analysis. The future research is presumed to describe a similar research strategy but investigates other social media platforms. In addition, this research dictated several factors that can affect the level of engagement on Instagram. Hopefully, future research will examine additional factors that can influence a company's marketing to achieve its marketing objectives and implementation over a more extended time.